PELAKSANAAN PEMASARAN KULINER KHAS MELAYU RIAU GALAMAI DI TOKO OLEH-OLEH BU ASTI KABUPATEN KUANTAN SINGINGI KECAMATAN KUANTAN TENGAH - Hariadi Noprison; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
One of the souvenir shops located in the center of the city of Taluk Kuantan is store Bu Asti. This study aims to describe how the implementation of Riau's typical Malay culinary marketing at store Bu Asti. Bu Asti's shop marketing activity uses the four P marketing mix concept, namely 1) Products (taste, food color, food aroma, food texture, food form, and packaging), 2) Price (food menu price), 3 ) Promotion (social media), 4) Place (strategic location). Store Bu Asti is one of the places that provides souvenirs which are typical culinary delights of Riau. Data obtained through field interviews and documentation. The results obtained from this study that shop souvenirs Asti has a marketing implementation that has a good effect on the seller.Keywords: Malay Typical Culinary, Marketing Mix, Marketing Implementation